Feminist Collections, v.18, no.2 (winter 1997) - (:unkn) unknown (My University, 1997)
Subtitle: A Quarterly of Women's Studies Resources. 42p.
Contents: Special Issue on Girls and Young Women. FROM THE EDITORS. BOOK REVIEWS: When the Seen and Not Heard Start Shouting: Listening to Young Women, by Ednie Garrison. Young, Female, and Sexually Active in the 1990s, by Deborah L. Siegel. RECENT BOOKS BY, FOR, OR ABOUT GIRLS AND YOUNG WOMEN. READING FOR REAL: MAGAZINES FOR GIRLS AND YOUNG WOMEN, by Megan Scanlon. FEMINIST VISIONS: Give Me That Camera! Playing with Gender in Videos about Girls, by Lisa Parks. FEMINIST PUBLISHING. WORLD WIDE WEB REVIEWS: FUNDING SOURCES FOR WOMEN, by Elizabeth Breed. COMPUTER TALK: Compiled by Linda Shult. WISCONSIN BIBLIOGRAPHIES IN WOMEN'S STUDIES. ARCHIVES. NEW REFERENCE WORKS IN WOMEN'S STUDES: Reviewed by Phyllis Holman Weisbard and others. PERIODICAL NOTES: Compiled by Linda Shult. ITEMS OF NOTE: Compiled by Renee Beaudoin. BOOKS RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews; Girls; Funding Sources; Young women; Grants; Girls' magazines